Fluid dynamics of the human aortic valve - Ireni Venugopal. (2008)
In the recent decades it has been renowned that cardiac diseases are the most deadly diseases throughout the world and of that the diseases pertaining to the valves are proportionately low but are significantly higher in number. The study and analysis of valvular flow dynamics is very significant in the clinical scenario. Based on such motivation, here in this research, the investigations are focused on the fluid flow dynamics of the aortic valve. The present project elucidates the velocity and pressure distributions in the normal aortic valve. The velocity profiles are investigated during the opening phase of the aortic valve with the model of Bellhouse of the aortic valve placed in a pulsatile water-tunnel.